Over a million students use our free study notes to help them with their homework
y=x2+2x-3
Can solve using quadratic equation. Using the square method to obtain for the square term and x term (x+1)(x+1) = x2+2x+1
Therefore (x+1)(x+1)-4=y
To f...
Increase the powers of all variables by one and then divide them by this number. For example, given 3x^3 + 5x^-0.5 - 8 , this would give 3/4x^4 + 10x^0.5 - 8x
First of all key elements required for this question is the knowledge or retrival of these equations: tan2 + 1 =sec2 A tan(A-B) = (tanA-tanB)/(1+tanAtanB) so for the first equation...
To answer this we will need to use the product rule which is as follows: For y=uv, dy/dx=u'v+uv' where u' is the derivative of u and v' is the derivative...
Integrate by parts. First rewrite the integral in the form udv/dx, which is (1)ln(x). Then integrate (1)ln(x) wrt dx by assigning u=ln(x) du/dx=1/x and dv/dx=1 v=x. We can determine the integral of ln...
←
365
366
367
368
369
→
Internet Safety
Payment Security
Cyber
Essentials